The Effect of Foreign Ownership, Tax Burden And Exchange Rate On Transfer Pricing With Company Size Moderation - Tito Malindo; Nurrohman Hari Mulyono (Faculty of Economics, Merdeka University Surabaya, Indonesia, 2025)
This Scholarly work offers novelty by exploring the Shaping force of foreign ownership, tax burden, and exchange rates on transfer pricing practices, while incorporating company size as a moderator. The Scholarly work mission is to examine the extent to which internal and external factors shape managerial decisions regarding transfer pricing strategies in multinational companies in Indonesia. A quantitative approach using Structural Equation Modeling (SEM) techniques was chosen to uncover the direct Interrelations and Modifying Repercussions between variables. The Scholarly work population comprised all consumer goods companies listed on the Indonesia Stock Exchange (IDX), with 45 companies selected as samples through a purposive sampling approach. The results reveal that tax burden and exchange rates significantly Shaping force transfer pricing, while foreign ownership exhibits no significant Shaping force. Company size is shown to moderate the Repercussion of tax burden on transfer pricing, but is not strong enough to Shaping force other Interrelations. The implications of this Scholarly work highlight the urgency of strict oversight of companies burdened with high taxes and facing exchange rate volatility. Theoretically, these revelations broaden the horizons of agency theory to address cross-border issues and corporate governance. The novelty of this Scholarly work lies in the inclusion of firm size as a moderating variable, which opens up fresh perspectives on how scale and corporate governance can curb transfer pricing aggressiveness in the global business arena.